(untitled) (Південний архів (історичні науки), 2025)
This article presents an archaeographic publication of archival documents that outline the land policy of the Kherson local self-government in the early 20th century. The aim of the study is to introduce into scholarly circulation a set of documents reflecting the administrative decisions of the Kherson City Duma and the municipal board regarding the management and use of urban land. The methodological foundation of the research is an archaeographic approach, which involves the scholarly processing, systematization, and annotation of archival materials. The main content consists of documents from Fund 4 of the State Archive of the Kherson Region, illustrating mechanisms of land-use regulation, approaches to land leasing, sales, and inventory within the city limits. The publication includes official correspondence, minutes of meetings, land contracts, and decisions of the Duma and the board, which reveal key aspects of land policy, including the procedures for leasing urban land, land inventory and audits, regulation of relations with tenants, determination of rental rates, prevention of unauthorized land use, and initiatives aimed at modernizing municipal land ownership. Particular attention is given to documents related to changes in land policy during World War I, especially concerning resource mobilization and their use by the military. The publication is supplemented with scholarly apparatus that includes commentary, explanations of terms and institutions, and references to the storage locations and catalog details of the documents. The conclusion highlights the importance of these materials for understanding the practical activities of local self-government bodies in the field of land policy during the prewar and wartime periods of the early 20th century. The documents presented here can serve as a foundation for further research into the socio-economic history of southern Ukraine, particularly clarifying the features of municipal governance in the city of Kherson.